Brain organoid methodologies to explore mechanisms of disease in progressive multiple sclerosis - Simões-Abade, Madalena B. C.; Patterer, Marlene; Nicaise, Alexandra M.; Pluchino, Stefano (Frontiers in Cellular Neuroscience, 2024)
Multiple sclerosis (MS), a debilitating autoimmune disorder targeting the central nervous system (CNS), is marked by relentless demyelination and inflammation. Clinically, it presents in three distinct forms: relapsing–remitting MS (RRMS), primary progressive MS (PPMS), and secondary progressive MS (SPMS). While disease-modifying therapies (DMTs) offer some relief to people with RRMS, treatment options for progressive MS (pMS) remain frustratingly inadequate. This gap highlights an urgent need for advanced disease modeling techniques to unravel the intricate pathology of pMS. Human induced pluripotent stem cell (iPSC) technologies and brain organoids are emerging as promising tools for disease modeling in both 2D and 3D in vitro environments. These innovative approaches enable the study of disease mechanisms that closely mimic human pathophysiology and offer new platforms for screening therapeutic compounds, surpassing the limitations of traditional animal models. However, deploying brain organoids in disease modeling presents challenges, especially in the context of non-monogenic disorders. This review delves into cutting-edge brain organoid techniques that hold the potential to revolutionize our understanding of pMS, offering a pathway to disentangle its underlying mechanisms and drive transformative discoveries.